(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
"When we learn how to become resilient, we learn how to embrace the beautifully broad spectrum of the human experience."-Jaeda Dewalt Across the globe, working dynamics are quickly evolving, with many organisations trying to navigate through unfolding business complexities. Especially the impact of the pandemic intensifies, business systems are tested more than ever before. All sectors have been impacted in some way, and all businesses must adapt to the current challenges, as well adjusting to a period of recovery.The concept of resilience has gained new momentum; it is very promising concept to explain how organizations can survive and thrive amidst adversity or turbulence. You need to e.nsure that your systems are resilient enough to maintain your business in this unpredi tab environment and support the reinvention of your organization as we move beyond the curr crisis. During the pandemic; it was observed that the business models abruptly altered. anrl in a short span chime, the management had to address, plan and execute the things seamlessly. It has become important for the management to bolster the financial resilience of th organisations through continuous transitions and transformation in their strategies. In this dynamic and uncertain world, resilience and innovation are the keys to survh firmly believe in resiliency and reinvention. According to me all the leaders will be su if they place empathy at the heart of their decisions. The conference provides a premier interdisciplinary platform for researchers, pmctiti ners an educators to present and discuss the most recent innovations, trends, and concerns as " n as practical challenges encountered and solutions adopted in the fields of building resilience an working towards the same.I am delighted with the overwhelming response from authors and thnnkful to then, fi r th ·, contributions. I wish good luck for the TIPSCON-2022.